Fiesta vs. Stress Condition the Incidence and the Age at Menarche. Forty Years of Research - Valenzuela, Carlos Y (Clinical Journal of Obstetrics and Gynecology, 2025)
Introduction: The annual rhythm of menarche was proposed to be due to climatic annual variations. The discovery that peaks of incidence of menarche were found in the same months in the North and the South Hemispheres made us to think this hypothesis was not correct. Then we proposed that periods of study (stress) and vacation (relaxation, fiesta) were better factors for this rhythm. If this is so, days of fiesta should present more menarches than current days. In the second hypothesis the age at menarche should be modified by the vacation-study rhythm. Thus, I tested two hypotheses: I) This rhythm and the age at menarche are conditioned by climate factors mostly seasonal variations. II) the contrast between expectancy of fiesta (relaxation) and stress is the main factor of the rhythm and the variation on the age at menarche during the year. Method: The monthly incidence and age at menarche were obtained from samples of girls in Santiago (Chile), Medellín (Colombia), Debrecen (Hungary), Chennai (India) with data collected directly in these countries. A sample from Barrinhas (Riberao Preto, Brazil) was taken from literature. The climatic hypothesis was tested knowing the main climatic parameters by the latitude of these cities. The annual study-vacation rhythm was obtained from the academic calendar at any city and from direct information of our colleagues working in these cities. A correlate between the climatic rhythm and the study-vacation rhythm with the incidence or age at menarche complete the refutation or affirmation of the hypotheses. Also, the expected peaks of menarche at significance fiesta-days or the birthday were studied directly form the calendar of holidays or the cultural information given by our colleagues. Results: In the five samples taken individually or together there were clear contradictions with the climatic hypothesis. On the contrary the fiesta-stress hypothesis shows a clear correlation with the monthly incidence and the age at menarche. Days of national, religious fiesta or the birthday showed greatly significant peaks of menarche. Conclusion: Data refute the climatic hypothesis of the annual rhythm of menarche and agree with the fiesta (vacation)-stress (study) hypothesis.